Incidence and Risk Factors of Neural Tube Defects in Kashan, Central Iran - TALEBIAN, Ahmad; SOLTANI, Babak; SEHAT, Mojtaba; ZAHEDI, Abolfazl; NOORIAN, Akram; TALEBIAN, Motahhareh (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Talebian A, Soltani B, Sehat M, Zahedi A, Noorian A, Talebian M. Incidence and Risk Factors of Neural Tube Defects in Kashan, Central Iran. Iran J Child Neurol. Summer 2015;9(3):50-56. Abstract Objective Neural tube defects (NTDs) are the most common congenital defects of central nervous system due to neural tube closure deficit during the third and fourth weeks of gestational age. Our study was performed to detect the incidence and risk factors of NTDs in Kashan, center of Iran. Material & Methods This case-control study was done on all pregnancies with NTD affected neonates (n=91) and 209 pregnancies with normal neonates from February 2007 to December 2012 in three hospitals in Kashan, center of Iran. Annual and the mean incidence of NTDs were calculated. Risk factors including neonatal gender, maternal age, gravidity, maternal abortion history, maternal gestational diabetes (GDM), folic acid use, familial marriage, maternal body mass index (BMI), birth season and family history of NTDs were evaluated by interview with mothers. Univariate and multivariate logistic regression were used to analyze the risk factors. Results The mean incidence of NTDs was 2.33 per 1000 births. The multivariate analysis indicated that maternal history of abortion (OR: 4.9, CI: 1.9-12.8), and maternal obesity (OR: 5.4, CI: 1.3-21.8) were significantly associated with NTDs. Conclusion Maternal history of abortion and BMI were the major risk factors of NTDs.